Analysis of Students' Statistical Literacy Ability Based on Learning Anxiety : A Phenomenological Study in High School Students - Rahmania, Fadhilah; Nuriadin, Ishaq (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze students' mathematical literacy skills based on learning anxiety aspects. The research method used is phenomenology with a qualitative approach. Data collection techniques through mathematical literacy tests, learning anxiety questionnaires, observation and in-depth interviews. The subjects of this study are 7 students of MAN 2 East Jakarta who were selected based on purposive sampling techniques from the aspect of learning anxiety. The data analysis used is an interactive model from Miles and Huberman which has four main stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study show that learning anxiety, especially in cognitive and behavioral aspects, has a significant effect on statistical literacy ability. Learners with low anxiety showed better literacy achievement, while those with high anxiety tended to have difficulty understanding and applying statistical concepts. These findings emphasize the importance of anxiety management in mathematics learning to improve students' statistical literacy. Therefore, adaptive learning approaches and psychological support are needed to help learners overcome anxiety and improve their literacy skills.